Novel phthalocyanines with naphthalenic substituents - Sener, M. Kasim; Gul, Ahmet; Kocak, Makbule Burkut (SPRINGER, 2008)
Phthalocyanines with four naphthyl-malonic ester groups on the periphery were synthesized by cyclotetramerization of 4-(1,1-dicarbethoxy-2-(1-naphthyl)-ethyl)-phthalonitrile. The new compounds were characterized by spectroscopic methods. The electronic spectra exhibit intense pi-pi* transitions from the naphthyl moiety together with the characteristic Q and B bands of the phthalocyanine core. The electrochemical properties of the 2,9,17,23-tetra-(1,1-(dicarbethoxy)-2-(1-naphthyl)-ethyl) phthalocyaninato copper(II) complex were studied by cyclic voltammetry.
Keywords: SOLUBLE PHTHALOCYANINES; METAL-FREE; METALLOPHTHALOCYANINES; OXYGEN; Chemistry